Analysis of the Role of the Land Agency in Handling Land Disputes and Social Conflicts Between PT. Bahruni & Sons and the Communities in Gampong Krueng Simpoe and Rantoe Panyang, Bireuen Regency - Zuhra Zuhra; Mohd Tasar (Journal of Social Research, 2026)
Land disputes involving plantation companies and local communities often develop into complex and prolonged social conflicts. One of the agrarian conflicts that until now has not found a solution occurred between PT. Bahruni & Sons with the communities of Gampong Krueng Simpoe and Rantoe Panyang, Bireuen Regency. This conflict is related to the issue of legality and the extension of the Right to Use (HGU) on oil palm plantation land that has been managed by the company since the 1960s. This study aims to analyze the role of the Bireuen Regency Land Office in handling land disputes and accompanying social conflicts. The research used a descriptive qualitative approach with a case study method. Data was obtained through interviews with Land Office officials, documentation studies in the form of official meeting minutes, and review of licensing documents and land tenure chronology. The results of the study show that the Land Office has carried out its role as a facilitator, mediator, and coordinator in the dispute resolution process. However, this role has not been optimally run due to differences in interests between the parties, low public trust, and historical and social complexity of land tenure. This research emphasizes the importance of strengthening the mediation function of local governments and the application of good governance principles in resolving agrarian disputes